2012
DOI: 10.1155/2012/697563
|View full text |Cite
|
Sign up to set email alerts
|

Functional Movement Is Negatively Associated with Weight Status and Positively Associated with Physical Activity in British Primary School Children

Abstract: Although prior studies have suggested that overweight and obesity in childhood are associated with poorer functional movement performance, no study appears to have examined this issue in a pediatric population. The relations between BMI, ambulatory physical activity and functional movement screen (FMS) performance were compared in 58, 10-11-year-old children. Total FMS score was significantly, negatively correlated with BMI (P = .0001) and positively related to PA (P = .029). Normal weight children scored sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
99
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(120 citation statements)
references
References 12 publications
15
99
5
1
Order By: Relevance
“…Conversely, data presented by Parchman and McBride [14] reported no significant association between FMS scores, golf club head speed, and various fitness tests in 25 adult golfers. Other research with a non-athletic child population has also reported that FMS scores were significantly related to body mass index [15], with higher BMI being associated with poorer FMS performance. Despite this data, few studies have examined how these functional movement patterns develop in adolescents generally and no studies to date have examined if and how FMS performance might be associated with anthropometric factors and performance in adolescent athletes.…”
Section: Introductionmentioning
confidence: 79%
“…Conversely, data presented by Parchman and McBride [14] reported no significant association between FMS scores, golf club head speed, and various fitness tests in 25 adult golfers. Other research with a non-athletic child population has also reported that FMS scores were significantly related to body mass index [15], with higher BMI being associated with poorer FMS performance. Despite this data, few studies have examined how these functional movement patterns develop in adolescents generally and no studies to date have examined if and how FMS performance might be associated with anthropometric factors and performance in adolescent athletes.…”
Section: Introductionmentioning
confidence: 79%
“…This may help explain, at least in part, the greater risk for skeletal fracture in obese children and adolescents [4, 5]. Whereas this elevated fracture risk may also be attributed to deficits in physical function and greater subsequent risk for falling [6], in vitro mechanisms implicating adipose tissue as a negative determinant of adolescent bone structure and strength have been shown in vivo [79]. …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have documented influences such as sedentary behaviour and nutritional habits on weight status but few have examined the structural and functional limitations of excess weight [3,4]. These studies have predominantly been in adult samples and few data have been reported for pediatric populations [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have documented influences such as sedentary behaviour and nutritional habits on weight status but few have examined the structural and functional limitations of excess weight [3,4]. These studies have predominantly been in adult samples and few data have been reported for pediatric populations [3,5]. This is somewhat surprising as children display alterations to their functional movement as a consequence of excessive weight [5] which can impede daily physical activity level and limit functional performance [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation